VÓRTICES BPS COM FLUXO MAGNÉTICO FRACIONÁRIO NO MODELO PADRÃO ESTENDIDO - Mentech, Guillermo Lazar (2013)
We study the existence of Abrikosov-Nielsen-Olesen-like BPS vortices in the context of the Standard Model Extension (SME). Specifically, we analyze the Maxwell-Higgs model supplemented by Lorentz-violating (LV) terms in both sectors. The LV terms of the Higgs sector are CPT-even, on the other hand, the gauge sector includes CPT-even and CPT-odd LV terms. One important consequence is the effect of the LV coefficients of the Higgs sector on the magnetic flux, it now is fractional. Among other effects, the LV coefficients are accounted by the control of the amplitude and the spatial extension of the topological defects. The first model analyzed includes a Lorentz-violating CPT-odd or Carroll-Field-Jackiw term in the gauge sector. The BPS equations under appropriated coordinate rescaling and field redefinition are the ones of the Maxwell-Chern-Simons-Higgs (MCSH) model. However, the difference appears in Gauss s law which contains a parameter dependent on LV coefficients of the Higgs sector. Such parameter when fixed to be 1 reproduces the Gauss law of the MCSH model. The second model studied contains the LV CPT-even term in the electromagnetic sector. It provides a new class of BPS vórtices. Here the parity-odd coefficients couple the magnetic and electric sectors yet in stationary regimen. Then, with the appropriate BPS potential the model engenders electrically charged BPS vórtices. This new BPS vortex solutions also supports electric field inversion and localized magnetic flux reversion.